Die Klosterwüstung Hopels - Bärenfänger, Rolf (Archäologische Denkmäler zwischen Weser und Ems, 2000)
Keywords: hopels

Die Konservierung des Apostelaltars im Ratzeburger Dom - Beetz, Alwin (Denkmal! Zeitschrift für Denkmalpflege in Schleswig-Holstein, 2000)
Keywords: ratzeburg

Gerlachsheim: katholische Pfarrkirche Heilig-Kreuz, ehem. Prämonstratenserklosterkirche. - Betz, Jutta (Peda-Kunstführer, 2000)
Keywords: gerlachsheim

Spurensicherung: Voraussetzung und notwendige Ergänzung kunstwissenschaftlicher Analysen ; zum Kruzifixus des ehemaligen Prämonstratenser-Klosters in Cappenberg - Endemann, Klaus (Unter der Lupe: Neue Forschungen zu Skulptur und Malerei des Hoch- und Spätmittelalters ; Festschrift für Hans Westhoff zum 60. Geburtstag, 2000)
Keywords: cappenberg

Zur Geschichte des Prämonstratenserstifts Gramzow - Enders, Lieselott (Jahrbuch für Berlin-Brandenburgische Kirchengeschichte, 2000)
Keywords: gramzow

Me peperit ecclesia mater. Einige Bemerkungen zur Selbstdarstellung Hermanns von Köln in seinem Opusculum de conversione sua - Gäbe, Sabine (Analecta Praemonstratensia, 2000)
Looking at the Opusculum from a literary studies perspective (form, stylizing, stereotyped attitudes, intention, reader’s point of view) one arrives at the following results: The descriptio historiae consists of a continuous description of the internal, spiritual, and intellectual struggle of the autobiographical ego. Individual experiences of his life are only reported in so far as they are important for the progression of conversion. „Historical Persons“ mentioned in the text do not have their own personality: Jews are stylized as adversaries of the conversion (according to the stereotyped attitudes stemming from the theological tradition). Christians, however, are made into role models. The identity of the autobiographical writer is the identity of an ordained Christian priest. His former Jewish identity is portrayed as „non-identity“. The intention of the work is not to be, as it was assumed in the past, a defence against the reproach that the conversion took place for opportunistic reasons. Nor is it an attempt to respond with anti-Semitic comments to latent hostile feelings against the former Jew. On the contrary, the intention is to show Christian readers an example of how to part Jews from their „hardening“ and win them for Christianity by gentleness and charity. The work attempts, as the second Crusade quickly approaches (among other things) to support efforts that defend Jews from encroachments.
Keywords: 👤 hermann of cologne

Urkundenbuch der Klöster Altenberg (Lahn-Dill-Kreis), Dorlar (Lahn-Dill-Kreis), Retters (Main-Taunus-Kreis) - Hardt, Albert (A. Hardt, 2000)
Keywords: altenberg; dorlar; retters

Die Verpachtungsbücher der Abtei Hamborn 1427-1616. Die Akten Kloster Hamborn 187 A, 187 B und 187 C im Hauptstaatsarchiv Düsseldorf (meist rekonstruiert aus dem Nachlaß Dr. Franz Rommel) mit Ergänzungen aus anderen Archivbeständen - Horstkötter, Ludger (Quellen und Materialien zur Hamborner Geschichte, 2000)
Keywords: hamborn

Norbert von Xanten: Vom Rheinland nach Magdeburg. Ein Europäer des 12. Jahrhunderts im Dienst von Kirche und Staat - Horstkötter, Ludger (Mitteldeutsches Jahrbuch für Kultur und Geschichte, 2000)
Keywords: 👤 norbert of xanten

St. Martin in Zyfflich: Gründungs- und Ausbauphase eines niederrheinischen Stiftes im Mittelalter - Keppler, Frank (Beiträge zur Chronik Zyfflichs, 2000)
Keywords: zyfflich

Zum Ordensrecht der Prämonstratenser bis zur Mitte des 12. Jahrhunderts - Krings, Bruno (Analecta Praemonstratensia, 2000)
This study presents an until now unknown original text of the first review of the Premonstratensian statutes from the year 1154/55 following the Munich manuscript Clm 1031 originating from the abbey of Windberg. The oldest statutes of the order, edited by R. Van Waefelghem, have been ratified in 1130 during the first general chapter and were confirmed by Pope Innocent II on petition of the founder himself, Norbert of Xanten. A decree of the general chapter from about 1140, concerning the whole order and regulating the dissolution of the double monasteries, has never existed. The famous decree, which prohibeted the further admission of women into the double monasteries, cannot have been issued by the general chapter before 1155. Probably it did not exist until the occidental schism (1159-1177). 22 decrees from 1140 to 1153 as well as the special statutes for the converses from 1154 are published about the above mentioned Munich manuscript.
Keywords: 📚 premonstratensian (general)

Die Geschichte der Grafen von Cappenberg und ihrer Stiftsgründungen Cappenberg, Varlar und Ilbenstadt - Leistikow, Andreas (Studien zur Geschichtsforschung des Mittelalters, 2000)
Keywords: cappenberg; ilbenstadt; varlar

Die himmlische Bibliothek im Prämonstratenserkloster Schussenried als literarisches Denkmal - May, Johannes (Marbacher Magazin, 2000)
Keywords: schussenried

Kloster Oelinghausen - 825 Jahre - Saure, Werner (Jahrbuch Hochsauerlandkreis, 2000)
Keywords: oelinghausen

Die letzte Prämonstratenserinnengemeinschaft von Kloster Meer: ein Bericht zur Wirtschaftssituation - Schildt-Specker, Barbara (Meerbuscher Geschichtshefte, 2000)
Keywords: meer

Der Prämonstratenserorden in Ratzeburg und Broda bei Neubrandenburg - Schirge, Alfred (Mecklenburgia Sacra, 2000)
Keywords: broda; ratzeburg

Zur Gründung des Klosters Grefrath (1177), zum Erbe der Gräfin Alverade von Maubach (1207) und zur Burg und Herrschaft Maubach - Tichelbäcker, Heinrich (Zwischen Jülich und Kurköln. Festgabe der Joseph-Kuhl-Gesellschaft zum 60. Geburtstag für Prof. Dr. Günter Bers, 2000)
Keywords: grefrath

Die ältesten Klostergesetzgebungen von Prémontré, Oigny, Cîteaux, Klosterrath und Arrouaise und ihre Beziehungen zueinander - Van De Perre, Dirk (Analecta Praemonstratensia, 2000)
The first chapter of this study is devoted chiefly to examining the relationship among the oldest monastic rules of Citeaux, Kloosterrade, Oigny and Prémontré, the examination showing that, for the chapters of those rules that are similar, there is line of dependence running from Citeaux to Prémontré to Oigny and from Kloosterrade to Prémontré to Oigny. This insight has also led to the conclusion that the oldest version of the Premonstratensian Rule is not the PW text and that a Px version must have existed of which the PW text is a later variant. Oigny did not copy the PW version, but rather a Px’ version, which is a hypothetical variant of Px. The second chapter goes into more detail about the reasons why, in the Premonstratensian Rule, the superior was called abbas (abbot) and the second in authority prepositus (provost). This is interpreted as a compromise between the German tradition, in which the superior was known as prepositus, and the French tradition, in which he was known as abbas. In the third chapter, lastly, an examination is made of the relationship among the rules of Prémontré, Citeaux and Arrouaise for lay brothers, and shows that the Rule of Prémontré was the oldest, a conclusion that is diametrically opposed to the recent position taken by C. Waddell that the Lay-brother Rule of Citeaux had already been drawn up around 1120 and was thus older than that of Prémontré. The examination also shows that, in its first edition, the Rule of Arrouaise adopted elements of the Premonstratensian Rule and was subsequently supplemented with elements from the oldest Lay-brother Rule of Citeaux and the later Rule of Prémontré.
Keywords: ⚖️ chapters and statutes

Die selige Gertrud von Altenberg und das Skriptorium im Kloster der Prämonstratenserinnen - Väth, Paul (Scrinium Berolinense. Tilo Brandis zum 65. Geburtstag, 2000)
Keywords: altenberg

Prämonstratenser-Chorherrenstift Geras, Stifts- und Pfarrkirche Maria Geburt und Ehem. Prämonstratenser(innen)kloster Pernegg, Stiftskirche zum hl. Andreas - Weiger, Alexander (Christliche Kunststätten Österreichs, 2000)
Keywords: geras; pernegg

Schola claustrum alterum dici debet. Filip van Harvengts raadgevingen aan studenten - Wouters, Jozef (Analecta Praemonstratensia, 2000)
In his letters to students, Philip of Harvengt († 1183) engages himself in a dialogue with the environment of the schools of his time. This is obvious since the exchange of letters was not an entirely private affair as it is nowadays. Letters were shared with one's companions and read by them. When Philip therefore wrote a letter to a student, he addressed in fact a broader public. The letters addressed to students appear to belong to two different literary types. His earliest letters, Ad Wedericum  and ad Hervardum  are in fact treatises concerning a debated question with some spiritual advise in the margin. Later written letters only contain spiritual advise. But all Philip's letters show a keen awareness of the fact that a sound exegesis starts from a litteral understanding of the material text of Sacred Scripture, even though he depicts its study as preparing for an experienced meeting with the  One who inspired it. This fundamental conviction concerning study of Scripture probably points towards influence from the Parisian school of the canons regular of Saint Victor. In his letter Ad Wedericum  Hugh of Saint Victor is explicitly quoted while Philip develops his argument in favour of a literal explication of the six days during which creation took place according to the book Genesis. "The school should be called another monastery", for, in spite of the different environment, assiduous study of Scripture is performed in both places. Bible study probably took on a different character in monasteries of  regular canons, such as Saint Victor in Paris and Bonne-Espérance, than the monastic lectio divina.
Keywords: 👤 philip of harvengt

Das Prämonstratenserkloster Adelberg in staufischer Zeit - Ziegler, Walter (Die Staufer, 2000)
Keywords: adelberg